PERSEPSI ORANG TUA TERHADAP PERKEMBANGAN KARIR ANAK PADA JENJANG SMP DI WILAYAH PRINGGOLAYAN KELURAHAN TIPES, SERENGAN, SURAKARTA TAHUN PELAJARAN 2021/2022. - Purnama, Santosa Rezi (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2022)
Abstract Parents are adults who bring children to adulthood, especially during development. The task of parents is to equip and prepare children for adulthood by providing guidance and direction that can help children in living life. And currently, during the pandemic, the education sector is also still running online systematically, therefore the control of children's learning is less able to be monitored by teachers. The role of parents is to assist children in learning, so that the child's learning process can be carried out properly. In providing guidance, the family has certain conditions that differ in style and nature from one family to another. Career is not only related to work, but also related to a series of activities carried out by a person during his life, including work, position, and education. Wherever children receive education, formal, informal or non-formal institutions, parents still play a role in determining the future of their children. Education is important to improve the way of thinking, independence and how to stand. This type of research was a descriptive qualitative approach. Due to reveal and describe the perspective of parents regarding child development. This research was conducted in the village of Pringgolayan, with the subject of parents who have new children sitting in junior high school. Data collection techniques using observation, interviews and documentation. then to check the validity of the data using triangulation of data sources and techniques. The results of the research were analyzed with the stages of data reduction, data presentation, and conclusions or verification. That the parents of junior high school children in the Pringgolaya area who were interviewed resulted in some of them agreeing with their children's career development and career preparation for their future, they also freed their children to determine what they wanted. they also support children by channeling their talents and interests into the things they want. However, there are also parents of students who do not really understand what career development is and there are those who think that children should be what their parents want, regardless of their children's wishes. These parents also force their children in the career development they want. Keywords: perception, parents, career development.